Everyman news [ the changing American front page - Weldon, Michele , 1958- (University of Missouri Press, 2008)
"Examines how newspapers have changed over the past few years, becoming story papers. Comparing 850 stories, story approaches, and unofficial sourcing in twenty American newspapers from 2001 and 2004, Weldon reveals a shift toward features over hard news, along with an increase in anecdotal or humanistic approaches to all stories"--Provided by publisher